Some Problems on Approximations of Functions (Signals) in Matrix Summability of Legendre Series - Sahani, Suresh Kumar; Mishra, Vishnu Narayan; Pahari, Narayan Prasad (Nepal Journal of Mathematical Sciences, 2021)
In this paper, we prove a main theorem dealing the matrix summability of Legendre series using non-negative monotonic non-increasing sequences of function. This paper is more general than [9], [12] and [22].